Membangun Manajemen Waktu Keluarga Yang Baik Bagi Ibu Rumah Tangga Dalam Usaha Peningkatan Ekonomi Keluarga - Putri Mauliza; Zahara Meutia (Lembaga Pengembangan Kinerja Dosen, 2024)
This service aims to analyze how to build good time management for housewives. The implementation method used in this PkM activity is by conducting face-to-face meetings with participants consisting of housewives. Providing training and discussions as well as conducting live questions and answers. The training uses lecture, discussion and question and answer methods. This aims to increase participants' awareness and understanding of the importance of building educational institutions that have competence and competitive advantage. Meanwhile, in the evaluation or assessment stage, participants will be given feedback about the service program that has been implemented. In this case, it will be a consideration for the service team in order to provide benefits for Sei Krio housewives. Based on the results of the service activities for housewives, suggestions are given, including: 1. Be more enthusiastic, especially for housewives, so that the time they have can be used correctly and effectively. 2. To continue to actively participate in training and competency development activities. 3. Community service activities like this can be carried out regularly either in the same location or in different locations to increase thrifty and saving behavior for children.